Outcome of cataract surgery in eyes with uveitis - Singh, Kalpana; Shrestha, Smita; Manandhar, Anu (Nepalese Journal of Ophthalmology, 2019)
Purpose: To assess the outcome of cataract surgery in patients with uveitis without the use of prophylactic high dose (> 5-10 mg/day) systemic steroid. Method: A hospital based prospective study enrolling 64 eyes of 60 patients with uveitis and cataract from May 2013 to April 2014 having intraocular inflammation under control for at least 3 months preoperatively and underwent phacoemulsification with in bag placement of foldable acrylic intraocular lens (IOL). Results: Twenty six male and 34 female were included with mean age of 47.23 ± 16.85SD (16-85) years. In 43.75 % of eyes the uveitis was idiopathic followed by sarcoiduveitis (18.7%), Herpetic uveitis (15.6%), Tubercular uveitis (6.2%), VKH (4.6%), HLAB 27(4.6%), Behcet’s, endogenous endophthalmitis, Wegener’s granulomatosis and lepromatous uveitis (1.5% each). Anterior chamber cell count was grade 1+ in 33 eyes (51.56%) on 1st post-operative day and in 29 eyes (45.31%) on second follow up. Out of total 11 eyes (17.18%) that developed fibrin, 7 eyes were treated with subconjunctival injection of dexamethasone with half hourly topical steroid drops. Other 4 eyes that developed fibrin responded to half hourly topical steroid. Dose of oralprednisolone increased in 6 patients in early post operative duration. At the final follow up, 50 eyes (92.58% ) had improvement in best corrected visual acuity and cystoidmacular edema (CME) in 5% (n=3) eyes. Conclusion: Even without the use of preoperative high dose of oral steroid, inflammation was under control with significant improvement in visual acuity 3 months postoperatively.